ON THE MECHANICAL PROPERTIES OF COMPOSITE MATERIALS INFLUENCED BY HEAT TREATMENT - Minodora Maria PASARE; Radostin DIMITROV (Fiabilitate şi Durabilitate)
Composite materials represent a category of new materials, with superior properties, used in many fields of activity. In the present work, reference is made to such a material, this material being studied under certain conditions, in order to highlight its special properties.